The Anatomical variations of artery of angular gyrus - Bartosz Niemiec; Zuzanna Guzowicz; Kacper Bluczak; Zuzanna Białkowska; Jakub Buczek; Maciej Samczuk; Aleksander Daniluk; Kaja Iwaniuk; Hubert Stachowicz; Jan Ostański (Kazimierz Wielki University, 2024)
Context: Angular gyrus is an anatomical structure of the brain located in the parietal lobe, taking part in writing and reading, language-use, memory and attention and spatial recognition. It is supplied by the angular gyrus artery, which is one of the caudal branches of the middle cerebral artery. One of the clinical pathologies of the angular gyrus artery is the ischemic stroke of the angular gyrus in the dominant hemisphere, responsible for the presence of Gerstmann Syndrome: left-right disorientation, agraphia, alexia, acalculia and finger agnosia. This systematic review aims to present the variety of anomalies of the main cerebral artery and the angular gyrus artery. Objective: Preparing a systematic review of papers describing the course anomalies of the angular gyrus artery. Materials and methods: PubMed and Google Scholar electronic databases was searched for phrases: 'Angular gyrus artery', 'Artery of angular gyrus', 'Middle cerebral artery branches', 'Branches of middle cerebral artery', 'Gerstmann Syndrome' published between years 2015 and 2023. Also 3 papers published before 2000 were used. From the selected 30 papers, 6 were used to prepare this analysis. Results: The middle cerebral artery, from which arises the angular gyrus artery, is marked by a significant variety of its division, mainly the number of the dividing trunks of the artery. Depending on the type of the division, the angular gyrus artery can arise from the upper, middle or lower trunk and vary in sizes. It can also appear as a singular or two separate branches. Instances of the anomaly of both the angular gyrus artery and posterior parietal artery are rare, but reported. Conclusions: The angular gyrus artery is characterised by a number of anomalies in its course, separation from the middle cerebral artery, diameter and branching.